The comparative study of mechanical properties of coconut shell as partial replacement of fine aggregate in concrete with different curing method - Lau, Jett Chen (2017)
Coconut is one of the most important agriculture products in Malaysia, after the coconut had been processed the coconut wastes were moved to the land fill. Coconut shell is one of the part from the coconut waste, it is very durable and it need a very long to biodegrade. Due to the slow biodegrade speed, the coconut wastes become one of the top of waste in Malaysia. The coconut Waste raises the landfill capacity in Malaysia. The coconut shell is very durable and hard so partial replace coconut as fine aggregate will reduce the land fill and also the pollution that cause by sand mining. The objective of this study is to analysis the effect of curing methods to mechanical properties of concrete by partial replaced fine aggregate as coconut shell with 3 different type of curing method (water, environmental, air dry). The test that had been carried out for the research are slump test, sieve analysis, compressive strength test, flexural strength test and splitting tensile test. This study is partial replaced the fine aggregate with coconut shell powder with 0%, 10% and 20% with 3 different type of curing method. The 20% of coconut shell powder concrete with water curing get the best compressive strength for day 60 which is 42.241kN/mm2 and flexural strength is 12.818kN/mm2. Water curing method get the best result next is air dry curing and the last is environmental curing. The coconut shell concrete got lower strength compare to normal concrete, however the CSC 10 and CSC 20 had been achieved the designed strength so the coconut concrete still able to use in construction. By reusing the coconut shell as partial fine aggregate replacement into concrete mix design, it reduce the amount of agriculture waste and reduce the usage of the sand.